The Price of Warm Glow - Andrew Lilley; Robert Slonim (Institute for the Study of Labor (IZA), 2013)
This paper presents a model and experimental evidence to explain the volunteering puzzle where agents prefer volunteering time to donating money when monetary donations are, ceteris paribus, more efficient for providing resources to charity. In the model agents receive heterogeneous utility from pure and impure altruism (Andreoni 1989) that permits warm glow to vary between monetary donations and volunteering, thus allowing preferences for impure altruism to rationalize inefficient allocation decisions. We define a measure of the price of impure altruism as the additional proportion of income sacrificed by a donor to give in the dimension that maximizes her utility, holding the overall charitable contribution constant. To test the predictions of the model we ran an experiment in which we varied within-subjects the costs and benefits of monetary and volunteer donations. We also primed between-subjects the emphasis on the donation value to the charity (pure altruism) or the sacrifice to the donor (impure warm-glow altruism). Consistent with the model's predictions, the experiment shows that priming pure altruism increases the efficiency of donation choices, substitutability of donations between money and time and crowding out. Nonetheless, while greater impurity results in a more inefficient allocation of resources, empirically we find it increases overall charitable donations. We discuss the implications of our experimental results for both theory and policy.
Keywords: D64; D78; H41; C91; 330; altruism; warm glow; volunteering; monetary donations; laboratory experiments